Evaluation of the efficacy of Arthrocare®for knee osteoarthrosis - Natalia Konstantinovna Zaigrova (Современная ревматология, 2013)
The paper gives the results of testing the efficacy of Arthrocare®(diacerein) in the treatment of osteoarthrosis (OA). The patients included into the investigation were divided into 2 groups. Group 1 took Arthrocare®and nonsteroidal antiinflammatory drugs (NSAIDs) as needed; Group 2 received NSAIDs only. Disease symptoms were reduced in both groups, as confirmed by better quality of life. In Group 1, there was a reduction in the degree of synovitis; in Group 2 the number of synovitis cases significantly unchanged. The rate of side effects and their magnitude were insignificant and required no treatment discontinuation in Group 1. In 3 patients from Group 2, NSAIDs were discontinued because of the symptoms of gastropathy. This study indicated that Arthrocare®was as effective as NNSAIDs and well tolerated. Arthrocare®treatment decelerated knee OA progression.